Space - Sirett, Dawn; Ward, Elle (London Dorling Kindersley Limited, 2019)
"Take your toddler on a pop-up space rocket adventure, and fly to the Moon in this lift-the-flap baby book with pictures that pop off the page! This imaginative pop-up peekaboo book follows two little astronauts, Daisy and Danny, who are rocketing into space and heading for their first Moon landing"--Bookseller's website (viewed June 2019)
English stories
2
Keywords: Astronauts -- Juvenile poetry; Astronauts -- Pictorial works